Does neonatal pain management in intensive care units differ between night and day? An observational study. Issue 2 (20th February 2014) - Guedj, Romain; Danan, Claude; Daoud, Patrick; Zupan, Véronique; Renolleau, Sylvain; Zana, Elodie; Aizenfisz, Sophie; Lapillonne, Alexandre; de Saint Blanquat, Laure; Granier, Michèle; Durand, Philippe; Castela, Florence; et al.
Abstract : Objective: To determine whether analgesic use for painful procedures performed in neonates in the neonatal intensive care unit (NICU) differs during nights and days and during each of the 6 h period of the day. Design: Conducted as part of the prospective observational Epidemiology of Painful Procedures in Neonates study which was designed to collect in real time and around-the-clock bedside data on all painful or stressful procedures. Setting: 13 NICUs and paediatric intensive care units in the Paris Region, France. Participants: All 430 neonates admitted to the participating units during a 6-week period between September 2005 and January 2006. Data collection: During the first 14 days of admission, data were collected on all painful procedures and analgesic therapy. The five most frequent procedures representing 38 012 of all 42 413 (90%) painful procedures were analysed. Intervention: Observational study. Main outcome assessment: We compared the use of specific analgesic for procedures performed during each of the 6 h period of a day: morning (7:00 to 12:59), afternoon, early night and late night and during daytime (morning+afternoon) and night-time (early night+late night). Results: 7724 of 38 012 (20.3%) painful procedures were carried out with a specific analgesic treatment. For morning, afternoon, early night and late night, respectively, the use of analgesic was 25.8%, 18.9%, 18.3% and 18%. The relative reduction of analgesia was 18.3%, p<0.01, between daytime and night-time and 28.8%, p<0.001, between morning and the rest of the day. Parental presence, nurses on 8 h shifts and written protocols for analgesia were associated with a decrease in this difference. Conclusions: The substantial differences in the use of analgesics around-the-clock may be questioned on quality of care grounds.